2015
DOI: 10.1097/mnh.0000000000000123
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic insights on the role of fibroblast growth factor 23 in cardiovascular disease

Abstract: Purpose of Review Fibroblast growth factor 23 (FGF23) regulates phosphate and vitamin D homeostasis and rises as kidney function declines. Animal studies have demonstrated direct and indirect effects of FGF23 that may promote heart disease. Herein we review the recent epidemiologic literature evaluating the relationship between FGF23 and cardiovascular disease. Recent Findings In observational prospective studies higher FGF23 associates with greater risk of incident cardiovascular disease including ischemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Mounting evidence revealed the close relationship between excess serum FGF23 and cardiac events and all-cause mortality in the CKD population [11][12][13][14] . While it is not merely a biomarker, research showed the biological relevance of elevated FGF23 and adverse outcomes: apart from dysregulated phosphorus metabolism, excess FGF23 could induce vascular calcification and myocardial hypertrophy in both klotho-dependent or -independent ways [15,16] . Based on the associations between the FGF23 and CVD in pathogenesis, the factor is expected to be a predictor with high specificity in CVD.…”
mentioning
confidence: 99%
“…Mounting evidence revealed the close relationship between excess serum FGF23 and cardiac events and all-cause mortality in the CKD population [11][12][13][14] . While it is not merely a biomarker, research showed the biological relevance of elevated FGF23 and adverse outcomes: apart from dysregulated phosphorus metabolism, excess FGF23 could induce vascular calcification and myocardial hypertrophy in both klotho-dependent or -independent ways [15,16] . Based on the associations between the FGF23 and CVD in pathogenesis, the factor is expected to be a predictor with high specificity in CVD.…”
mentioning
confidence: 99%
“…C-reactive protein serves as an excellent biomarker indicating low grade inflammation and together with several other cytokines (Tumor necrosis factor alpha, Interleukin 6) is associated with heart failure even in a doseresponse relationship [3,4]. Fibroblast growth factor-23, in combination with the modulating co-receptor α-Klotho, is a phosphationic hormone produced by osteocytes and regulates calcium and phosphate homeostasis which are cornerstones for bone integrity [5]. FGF23 was extensively studied in renal dysfunction and inflammation [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…FGF23 was extensively studied in renal dysfunction and inflammation [6][7][8][9][10]. Recently, FGF23 was associated with atrial fibrillation, left ventricular hypertrophy, as well as morbidity and mortality in heart failure [5,11,12]. However, most studies of FGF23 and heart failure are confounded by chronic kidney disease which is accompanied by disturbed mineral-, blood and Iron-homeostasis as well as inflammationall of them interacting with FGF23making it difficult to explain a direct role of FGF23 on the heart [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…14,2433 Like phosphorus, increased cardiovascular risk associated with higher FGF23 was reported in a wide variety of groups including those with ESRD, CKD, and the general population with the strongest risks in patients with CKD and ESRD. 34 Although FGF23 has been associated with many non-cardiovascular outcomes as well, 29,33,3538 some of the most commonly reported and robust associations are with heart failure. 34…”
Section: Introductionmentioning
confidence: 99%
“…34 Although FGF23 has been associated with many non-cardiovascular outcomes as well, 29,33,3538 some of the most commonly reported and robust associations are with heart failure. 34…”
Section: Introductionmentioning
confidence: 99%